The Siesta Habit is Associated with a Decreased Risk of Rupture of Intracranial Aneurysms - Kang, Huibin; Feng, Xin; Zhang, Baorui; Guo, Erkang; Wang, Luyao; Qian, Zenghui; Liu, Peng; Wen, Xiaolong; Xu, Wenjuan; Li, Youxiang; Jiang, Chuhan; Wu, Zhongxue; et al. (Frontiers in Neurology, 2017)
Background and Purpose—Previous studies have examined an association between the siesta habit and hypertension, coronary heart disease. There is no report about the relationship between siesta and intracranial aneurysm(IA) rupture at present. We conducted this study to identify the effects of siesta on the rupture of IA. Methods—We prospectively enrolled consecutive patients with IAs at our institution from January 2016 to December 2016. Univariate analysis and multivariate logistic regression analysis were performed to identify the independent risk factors associated with IA rupture. Results—581 consecutive patients with 514 unruptured and 120 ruptured aneurysms. Hypertension, hyperlipidemia, diabetes mellitus, cigarette smoking, location, size , shape and aspect ratio turned out to be associated with the rupture of IA onunivariate analysis. Multivariate analysis identified hypertension (odds ratio[OR], 1.68; 95% confidence interval[CI], 1.03-2.73), hyperlipidemia (OR, 0.25; 95%CI, 0.08-0.72), current cigarette smoking ≥20 cigarettes/d (OR, 3.48; 95%CI, 1.63-7.47), Siesta(siesta time＜1hours, OR, 0.49;95%CI, 0.24-0.98 and siesta time≥1hours;OR, 0.32; 95% CI, 0.19-0.57) , location on anterior communicating and internal carotid–posterior communicating artery of largest aneurysm(anterior communicating artery, OR, 16.27; 95%CI, 7.40-35.79 and posterior communicating artery, OR, 11.21; 95%CI, 5.15-24.43), and size ≥7mm (OR, 2.19; 95%CI, 1.21-3.97) as independent strong risk factors for aneurysm rupture. Conclusion—Habitual siesta is new protective factor for IA rupture risk assessment, siesta habits may reduce the risk of aneurysm rupture. We also found hypertension, hyperlipidemia, cigarette smoking, location and aneurysm size were associated with the rupture of IA.